Proposal of a Multilevel Competencies Model for Innovative Public Management - Montezano, Lana; Isidro, Antonio (Future Studies Research Journal: Trends and Strategies, 2020)
Considering the relevance of innovation for public organizations and that people are fundamental to generate innovation, there was an absence of the competence models necessary for innovative public management in Brazil, even with recommendations for the development of this type of model by the OECD. The objective was to propose a theoretical model of multilevel analysis of competencies for innovation in the Brazilian public sector. This is a theoretical essay based on the analysis of scientific publications and documentary research on competence and innovation models in the public sector. It was possible to establish premises and conceive a theoretical model of competencies for innovation in the public context, which is dynamic, systemic, multilevel and integrated, in order to allow the identification of the competences necessary to subsidize the competence management subsystems for innovation in the public sector. the improvement in the provision of services. Contributes to the proposal of a model for empirical tests in future studies.